The method of determination of material shear elasticity in the course of its solidification - Aktan, O.Yu.; Svechnikova, O.S.; Nikovaenko, T.Yu. (Functional Materials, 2007)
A method is proposed for investigation of solidification processes based on the shear moduls determination of the material being solidified. A procedure has been developed to calculate that quantity. The proposed method has been approved in experiment.